Strengthening maternal nutrition counselling during routine health services: a gap analysis to guide country programmes - Justine A Kavle (Cambridge University Press, 2023)
Abstract Objective: The WHO recommends counselling on healthy eating, weight gain, and physical activity during antenatal care (ANC) and postnatal care (PNC), yet advice and information are often not tailored to women's nutritional needs and contexts. The purpose of the gap analysis was to identify key elements related to the provision of maternal nutrition counselling during routine health contacts and provide programme considerations to strengthen quality service delivery. Design: A search of PubMed, Cochrane Library, CINAHL Plus and Scopus databases was conducted to retrieve studies from January 2010 to December 2021. Using inclusion criteria, quantitative, qualitative and mixed methods studies were included in the final gap analysis. Setting: Low-, middle- and high-income country contexts. Participants: Following application of gap analysis criteria, thirty-seven articles from sixteen countries were included in the analysis. Results: Gaps in delivery of maternal nutrition counselling include provider capacity building, frequency, content and delivery platforms. Globally, counselling on appropriate weight gain during pregnancy is often not delivered with the desired content nor quality, while targeted counselling to overweight and obese women was provided in several high-income country contexts. Delivery of maternal nutrition counselling through multiple delivery platforms demonstrated improvements in maternal diet and/or weight gain during pregnancy. Conclusions: Strengthening the integration of maternal nutrition counselling into pre- and in-service curricula, routine health provider training, supportive supervision and provider mentoring is needed. Future efforts may consider generating global and regional weight gain guidelines and incorporating maternal nutrition counselling indicators as part of quality-of-care ANC/PNC standards and routine health systems.